Evaluating Green Performance of Suppliers via Analytic Network Process and TOPSIS. (22nd April 2013) - Akman, Gülşen; Pışkın, Hamit
Abstract : Developments in environmental issues in the last few years have been forcing manufacturing companies to improve their environmental performances. Many firms developed integrated relationships with their suppliers to increase their environmental performance and to decrease their hazardous effects on the environment. Then, selecting suitable and green suppliers in the supply chain has become a key strategic consideration. A performance evaluation system for green suppliers is necessary to determine the suitability of suppliers to cooperate with the firm. Therefore, in this study, a model for evaluating green performance of suppliers is proposed, and a hybrid multicriteria decision making model is developed in order to evaluate green performance of the suppliers. The analytical network process technique is applied to handle the relationships and dependence of selection criteria and subcriteria and determine weights of the criteria. The technique for order preference by similarity to ideal solution is used to sequence the suppliers for ideal solution of the suppliers' green performance evaluation problem. After a comprehensive literature survey, evaluation criteria of green performance for suppliers are determined. Finally, green performance of 18 suppliers of an automobile company was evaluated by this model. These 18 suppliers manufacture chassis and its components.